The influence of epigenetics in cancer prevention (Research, Society and Development, 2022)
Epigenetics refers to chromatin-based mechanisms important in the regulation of gene expression that do not involve changes in the DNA sequence. This study aims to analyze the influence of epigenetics in the prevention of various cancers. This work is based on searches in scientific databases such as LILACS, SciELO and PUBMED in the last 5 years, with filtering in complete works in Portuguese and English. The results showed an analysis of cancers such as lung, colorectal, breast, bladder, esophagus and prostate. In conclusion, that DNA methylation patterns are erased in the early embryonic stage and reestablished in each individual at the time of implantation, with an greater study in the area of epigenetics, will make it possible to silence several genes that will prevent the development of cancer in different situations.